Simulating the effect of grain boundaries on microstructurally small fatigue crack growth from a focused ion beam notch through a three-dimensional array of grains. (15th June 2016) - Musinski, William D.; McDowell, David L.
Abstract: Microstructurally small crack (MSC) growth strongly depends on local microstructure and often displays oscillatory character in terms of crack growth rate (da/dN) as a function of the conventional stress intensity range due to crack tip/grain boundary interactions of MSCs. A fatigue indicator parameter (FIP)-based MSC growth model is presented for high temperature MSC growth in polycrystalline Ni-base superalloy IN100 that takes into account crack tip/grain boundary interaction. An expression for FIP evolution is evoked based on a sequence of finite element simulations for stationary cracks. The MSC growth model was fit to experiments within the context of a simple 1D crack growth model and then applied to model 3D crack growth from a simulated focused ion beam (FIB) notch. Simulations showed that the MSC growth rate became less oscillatory as the MSC front sampled more grains, and eventually converged to the LEFM response with further crack extension. Graphical abstract: